Educational Debriefing Related to Digital Marketing and Halal Certification to Juragan Dimsum’s MSMEs - Hadiyani, Sherry; Adnans, Abdhy Aulia; Ivana Putri; Muhammad Suriya Pratama; Nurjannah Angelina; Surbakti, Ahmad Maulana; Naumi, Cindy Aprilia (ABDIMAS TALENTA: Jurnal Pengabdian Kepada Masyarakat, 2022)
One of the pillars that has an important role in the Indonesian economy is Micro, Small Medium Enterprises (MSMEs). Juragan Dimsum is one of the MSMEs engaged in the culinary field and is located in Medan Tuntungan. Juragan Dimsum has been doing marketing through Instagram social media which is managed directly by the owner. However, the application of digital marketing is still not good enough. In addition, this business has not had halal certification for almost 5 years. As an effort to overcome these problems, community service is carried out by holding digital marketing training, product photo training, and providing education related to halal certification. Educational training and provision can help MSMEs of Juragan Dimsum to be different from other similar competitor businesses, and increase consumer trust and interest in business products. Educational training and debriefing carried out using lecture, demonstration, practice methods, as well as direct discussion and question and answer. The results of the implementation of community service show that the target audience can take part in the entire series of activities with a positive attitude, and have better stock in managing business, especially in social media.